Accuracy of remote chest X-ray interpretation using Google Glass technology. (15th September 2016) - Spaedy, Emily; Christakopoulos, Georgios E.; Tarar, Muhammad Nauman J.; Christopoulos, Georgios; Rangan, Bavana V.; Roesle, Michele; Ochoa, Cristhiaan D.; Yarbrough, William; Banerjee, Subhash; Brilakis, Emmanouil S.
Abstract: Objectives: We sought to explore the accuracy of remote chest X-ray reading using hands-free, wearable technology (Google Glass, Google, Mountain View, California). Methods: We compared interpretation of twelve chest X-rays with 23 major cardiopulmonary findings by faculty and fellows from cardiology, radiology, and pulmonary-critical care via: (1) viewing the chest X-ray image on the Google Glass screen; (2) viewing a photograph of the chest X-ray taken using Google Glass and interpreted on a mobile device; (3) viewing the original chest X-ray on a desktop computer screen. One point was given for identification of each correct finding and a subjective rating of user experience was recorded. Results: Fifteen physicians (5 faculty and 10 fellows) participated. The average chest X-ray reading score (maximum 23 points) as viewed through the Google Glass, Google Glass photograph on a mobile device, and the original X-ray viewed on a desktop computer was 14.1 ± 2.2, 18.5 ± 1.5 and 21.3 ± 1.7, respectively (p < 0.0001 between Google Glass and mobile device, p < 0.0001 between Google Glass and desktop computer and p = 0.0004 between mobile device and desktop computer). Of 15 physicians, 11 (73.3%) felt confident in detecting findings using the photograph taken by Google Glass as viewed on a mobile device. Conclusion: Remote chest X-ray interpretation using hands-free, wearable technology (Google Glass) is less accurate than interpretation using a desktop computer or a mobile device, suggesting that further technical improvements are needed before widespread application of this novel technology.